2018
DOI: 10.1016/j.infoecopol.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Transition from copper to fiber broadband: The role of connection speed and switching costs

Abstract: We estimate a mixed logit model using data on choices of broadband technologies by 94,388 subscribers to a single broadband operator in a European country on a monthly basis from January to December 2014. We find that valuation of DSL connection speed in the range between 1 and 8 MB/s is very similar. Moreover, in January 2014, the valuation of FttH connection with speed of 100 MB/s is not much different than of DSL connection with speed of 1 or 8 MB/s but it increased over time. The small initial difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Authors review the quality parameters of Internet access services. and suggest that the bandwidth of Internet connections tend to have significant positive and negative, respectively, effects on satisfaction of customers with the internet provider (Giovanis et al, 2014;Grzybowski et al, 2018). The connection speed is an extraordinarily important quality feature.…”
Section: Literature Review Customer Satisfactionmentioning
confidence: 99%
“…Authors review the quality parameters of Internet access services. and suggest that the bandwidth of Internet connections tend to have significant positive and negative, respectively, effects on satisfaction of customers with the internet provider (Giovanis et al, 2014;Grzybowski et al, 2018). The connection speed is an extraordinarily important quality feature.…”
Section: Literature Review Customer Satisfactionmentioning
confidence: 99%
“…CERRE, 2017), while other quality parameters, such as delay, jitter, and packet loss also profoundly affect customers’ quality of experience (Stocker & Whalley, 2018). Early empirical evidence also shows that bandwidth demand and the valuation of Fiber to the Home (FTTH) has grown significantly in recent years (Grzybowski et al, 2018). Considering this, we do skip the incubation period, and therefore model the adoption curve over time as a limited exponential growth function, defined as follows:…”
Section: The Modelmentioning
confidence: 99%
“…Fibre-wireless (FiWi) networks have evolved as a promising broadband access network as it offers a huge capacity of bandwidth from the fibre and freedom of mobility from the wireless side [1][2][3][4][5][6]. The survey conducted in [7] found that the European broadband subscriber valuation of fibre to the home (FTTH) connection has increased quickly over time and became significantly higher than the valuation of digital subscriber line at the end of the survey in December 2014. Furthermore, the number of FTTH subscribers in Europe increased by 20.4% since September 2016 with more than 51.6 million FTTH subscribers in September 2017 [8].…”
Section: Introductionmentioning
confidence: 99%